0 - Editorial - Olajide Oloyede, (African Sociological Review, 2019)
In this issue, we publish a paper on the minibus taxi industry in South Africa, which, by definition is an unscheduled public transport service operated on a specific route or routes. The minibus taxi is a “kombi” vehicle designed or modified solely or principally for conveying between 9 and 16 seated persons, including the driver. Much has been written and said about this industry in the print and electronic media in the country. The thuggery prevalent in the industry, which appears to emanate generally from the competitive nature of the industry and mostly around routes has been variously highlighted. Academic studies of the industry seem to be mostly by students for degrees at Masters and doctoral levels and is generally few. This picture provides the rationale for the journal to publish the paper, which was welcomed by the reviewers. What is known generally about the industry is that it dominates what is referred to as the land – based public passenger transport sector accounting, in one estimate, for approximately 70% of total transport usage. Bus and rail account for the remaining 30% share of land – based public passenger transport industry in South Africa with the former accounting for 20.1% and the later 9.9%. Of the 70% taxi total, minibus taxi industry accounts for approximately 63% while the metered taxi industry account for 7% of the total transport usage. The taxi industry in South Africa is largely informal but subjected to public transport regulations. It is the non – compliance of the aspect of these regulations that creates job insecurity for minibus taxi drivers that the paper, Employment Practices within the Minibus Taxi Industry in Johannesburg: A Study of Precariousness of Jobs in South Africa focuses upon. The author, Fobosi, uses the concept of ‘precarity’ to highlight the insecurities of jobs in the industry arguing that this will persist so long as the minibus taxi owners continues to flout the regulations.